Shyness and Adjustment in Early Childhood in Southeast China: The Moderating Role of Conflict Resolution Skills - Zhu, Jingjing; Fu, Rui; Li, Yan; Wu, Min; Yang, Tingting (Frontiers in Psychology, 2021)
The massive social change in urban China today has led to a decline in the adaptive implications of shyness for child adjustment yet evidence of this trend in young children is limited. Moreover, the underlying mechanisms that help to explain the associations between shyness and maladjustment remains poorly understood. The primary goal of the present study was to explore the moderating role of conflict resolution skills in the links between shyness and socio-emotional and school adjustment among urban Chinese preschoolers. Data were collected from 360 children (44.4% girls, Mage = 4.72 years, SD = .63) in kindergartens using parent ratings, teacher ratings, and child interviews. The analyses indicated that the relations between shyness and adjustment were moderated by child conflict resolution skills, which served to buffer shy children from adjustment problems. The results were discussed in terms of the implications of conflict resolution skills for early adjustment of shy preschoolers in the Chinese context.